Consequências da pandemia de Covid-19 nos procedimentos de saúde bucal realizados nas Unidades Básicas de Saúde de Manaus - Cecílio, Igor Miguel Lago (Brasil, 2022)
The first case of covid 19 was reported in Wuhan, China. Due to its high transmission rate, the high number of new cases and deaths, the Covid-19 Pandemic was decreed by WHO in March 2020. In order to halt the advance of the pandemic, health entities decreed sanitary measures of social distance. Like several layers of society, dentistry was impacted by these measures. Elective dental care was suspended in the Primary Health Care network, remaining only the care characterized as urgency. There were also numerous guidelines and recommendations about clinical care, including: preference for techniques that did not produce aerosols, longer intervals between visits, strict biosafety and use of PPE, among others. The present study aims to observe the consequences of the covid 19 pandemic on oral health procedures performed in the UBSs of Manaus, Amazonas. For this, an seccional, analytic study design was used, using secondary data provided by the information service of the Ministry of Health, therefore, it did not require an ethical opinion. Data were collected regarding extraction procedures, periodontal scraping and permanent tooth restoration, from January 2019 to July 2022, in order to analyze the moments before and during the pandemic. Were also gathered data regarding the sex and age group of users, as well as the type of demand: scheduled or spontaneous. Data analysis was performed in two stages using the SPSS software version 20.0. The first stage consisted of descriptive analysis stratified by gender, age group and type of demand. In the second stage, bivariate analysis was conducted to observe the differences between the averages of dental procedures by sex, age group, type of demand and moment of care, whether before or during the pandemic. For this analysis, the T-test for independent samples with a 95% confidence level was calculated. The results showed that in January 2019, 9,257 procedures were performed, while in January 2022 only 2,776 were performed. It is concluded, then, that consequences of the pandemic of covid 19 on oral health procedures performed in the UBSs of Manaus was observed the decrease in the number of procedures performed after the beginning of the pandemic, as well as the emergence of a repressed demand.